Mecanismos de acesso à moradia em áreas públicas - OLIVEIRA, Alex Silva de (2020)
The present study deals with the theme of the existing legal and political mechanisms that allow the application of the right to housing in public areas, considering the impossibility of using these assets (art.183, §3º, CF 88), in which some decisions court they grant usucaption in public goods and thus neglect the possibility of applying other instruments that could serve the same purpose in guaranteeing the social function of property and the realization of the fundamental right to housing, as p. ex: the special concession for housing purposes (CUEM), governed by Provisional Measure No. 2,220, September 4, 2001, also present, in art. 183, §1 °, CF / 88, and incorporated as an instrument of urban land regularization by Law No. 13,465 of July 11, 2017 (Reurb). Having as scope this theme, the study make a critical analysis of the evolution of the Brazilian legislation, since the invasion of Brazil by Portugal, going through the sesmarias, Land Law of 1850, the Federal Constitution of 1988 until the most recent Law of regularization urban (Reurb) with the purpose of understanding the historical reasons of the great Brazilian housing deficit and the importance of the creation of legal instruments capable of realizing the right to decent housing and analyzing how effective the existing mechanisms are.